1990
DOI: 10.1200/jco.1990.8.9.1543
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase I/II trial of hyperfractionated radiation therapy with total doses of 60.0 Gy to 79.2 Gy: possible survival benefit with greater than or equal to 69.6 Gy in favorable patients with Radiation Therapy Oncology Group stage III non-small-cell lung carcinoma: report of Radiation Therapy Oncology Group 83-11.

Abstract: A phase Ilate/II trial of hyperfractionated (HFX) radiation therapy for non-small-cell carcinoma of the lung (NSCCL) was conducted by the Radiation Therapy Oncology Group (RTOG) between 1983 and 1987. Fractions of 1.2 Gy were administered twice daily with greater than or equal to 4 hours between fractions. Patients were randomized to receive minimum total doses of 60.0, 64.8, and 69.6 Gy. After acceptable risks of acute and late effects were found, 74.4 Gy and 79.2 Gy arms were added, and the lowest total dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(86 citation statements)
references
References 0 publications
4
80
0
2
Order By: Relevance
“…Part of this paper was presented in the 47 th ASTRO annual meeting, October [16][17][18][19][20] 2005, in Denver, Colorado. The work at MSKCC was supported in part by NIH grant P01-CA59017.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of this paper was presented in the 47 th ASTRO annual meeting, October [16][17][18][19][20] 2005, in Denver, Colorado. The work at MSKCC was supported in part by NIH grant P01-CA59017.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Two-year local control is 30-50% for medically inoperable stage I-II NSCLC tumors treated with RT and 15-20% for locally advanced disease 16 . Several studies have shown that higher radiation doses correlate with improved local control [17][18][19] . However, treatment dose is limited by the dose-volume constraints of normal lung 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…everal studies [1][2][3] have shown that high-dose radiotherapy is an acceptable alternative to surgery in patients with inoperable nonsmall cell lung carcinoma (NSCLC). However, in most of these studies, patients were irradiated over large areas including not only the primary tumor but also regional lymph nodes in the hilum and mediastinum.…”
mentioning
confidence: 99%
“…11 Moreover, a variety of regimens of hyperfractionated radiation were tested, and survival improved for patients treated with the dose given in two fractions per day 31 or in a continuous hyperfractionated accelerated manner (CHART). 32 The choice of alternate chemotherapy and radiation therapy is supported by cytokinetic and pharmacologic data.…”
Section: Discussionmentioning
confidence: 99%